Evaluation of the lactic acid bacteria based formulated probiotic product for poultry - Al-Surrayai, T.; Al-Khalaifah, H.; Al-Mansour, H.; Kishk, M.; Al-Mutairi, A.; Sultan, H.; Al-Saleem, H. (Frontiers in Animal Science, 2022)
In this study, we evaluated the effectiveness of a probiotic product developed to reduce the effect of Salmonella infections and compared it to the effectiveness of commercial probiotics in selected broiler chicken farms. Based on the in vitro assessment of the growth characteristics and safety to human health, four bacterial isolates were obtained, characterized, and identified as excellent candidates for the development of commercial probiotic feed additives for poultry production in Kuwait. A preliminary study was conducted in which the selected isolates were evaluated individually in vivo with three different methods of application (water, feed, and oral gavage). The cycle included 312 chicks, which were divided into 13 groups, including control, distributed into four batteries. Each battery consisted of three levels, and an area of 0.85 m2 was provided to each bird. There were eight replicates with 24 chicks in each replicate, and the analyses were triplicated. The results helped in formulating the new probiotic product. The efficiency of the newly formulated product was assessed. In vivo evaluations were performed, and the newly formulated product was compared to two imported commercial products (Alterion and Galli pro fit) used in poultry farms in Kuwait. The cycle included 120 chicks that were divided into five groups, including control, and eight replicates with 24 chicks in each replicate; the analyses were triplicated. The results showed that the new product maintained the health of chickens, and no deaths were recorded, although antibiotics were not administered. Additionally, the vital signs were high, and all birds in different treatment groups gained a high mass of delicious meat, as determined by the results of the sensory evaluation.